A new blockchain and fog computing model for blood pressure medical sensor data storage. (September 2022) - Mani, Vinodhini; Ghonge, Mangesh M.; Chaitanya, Nosina Krishna; Pal, Om; Sharma, Moolchand; Mohan, Senthilkumar; Ahmadian, Ali
Abstract: The healthcare business can benefit from the Internet of Things (IoT) in terms of data management and transfer. Patient health data can be acquired locally from devices that can be used to make real-time decisions based on the data. For many years, several hospitals have deployed IoT in their patient rooms and their body parts. IoT devices could be vulnerable to hacking due to a lack of authentication and encryption policies, posing serious hazards to consumers. As a result, blockchain is useful for securing and proving transactions in the IoT. As a result, it is proposed that the problem be solved using Fog Computing (FGC), Edge Computing, and blockchain. Based on FGC technology, models of analysis, and a signature-encryption algorithm (SE), a three-tiered architecture is employed for the identification, verification, and identification of healthcare IoT devices. The generated findings are used to assess the suggested innovative SE algorithm. We discovered that FGC-based blockchain performed better for detecting malicious nodes in terms of packet error rate, reliability, and throughput when compared to cloud settings and other environments.